The application of instrumented falling weight impact test to determine the ductile-brittle transition in acrylate rubber-modified PVC - Hassan, Azman (1997)
The current trend in window frame applications shows the importance and popularity of high impact-acrylate modified PVC. The objective of this research is to extend the existing knowledge of toughness enhancement in rubber-toughened polymer materials to acrylate rubber-modified PVC, similar to compounds used in window frame applications. This paper reports the use of an instrumented falling weight impact test (IFWI) method to determine the ductile brittle transition in acrylate rubber-modified PVC-U. The results show that force and energy data from the IFWI test were sensitive to the filter level and optimum filter level for apparatus/specimen combination is thus necessary. The IFWI test have highlighted the difficulties which must be overcome to obtain accurate and reliable data in the determination of impact strength values at high impact velocities, for brittle specimens. The results also show that over the impact velocity range studied (i.e. 1 to 6 m/S) all the acrylate rubber-toughened PVC blends except blend M2 showed a transition from ductile to brittle at a temperature of around 20 degree C. The impact modifiers were found to differ in their efficiency to shift the ductile to brittle transition.